Opioid Prescribing Patterns Following Pediatric Tonsillectomy in the United States, 2009–2017. (7th October 2020) - Qian, Z. Jason; Alyono, Jennifer C.; Jin, Michael C.; Cooperman, Shayna P.; Cheng, Alan G.; Balakrishnan, Karthik
Abstract : Objectives: Assess national trends in opioid prescription following pediatric tonsillectomy: 1) overall percentage receiving opioids and mean quantity, 2) changes during 2009–2017, and 3) determinants of prescription patterns. Methods: Cross‐sectional analysis using 2009–2017 Optum claims data to identify opioid‐naïve children aged 1–18 with claims codes for tonsillectomy (n = 82, 842). Quantities of opioids filled in outpatient pharmacies during the perioperative period were extracted and converted into milligram morphine equivalents (MMEs) for statistical comparison. Demographic, clinical, and socioeconomic predictors of opioid fill rate and quantity were determined using regression analyses. Results: In 2009, 83.3% of children received opioids, decreasing to 58.3% by 2017. Rates of all‐cause readmissions and post‐tonsillectomy hemorrhages were similar over time. Mean quantity received was 153.47MME (95% confidence intervals [95%CI]: 151.19, 155.76) and did not significantly change during 2009–2017. Opioids were more likely in older children and those with higher household income, but less likely in children with obstructive sleep apnea, other comorbidities, and Hispanic race. Higher quantities of opioids were more likely in older children, while lower quantities were associated with female sex, Hispanic race, and higher household income. Outpatient steroids were prescribed to 8.04% of patients, who were less likely to receive opioids. Conclusion: While the percentage of children receiving post‐tonsillectomy opioids decreased during 2009–2017, prescribed quantities remain high and have not decreased over time. Prescription practices were also influenced by clinical and sociodemographic factors. These results highlight the need for guidance, particularly with regard to opioid quantity, in children after tonsillectomy. Level of Evidence: N/A Laryngoscope, 131:E1722–E1729, 2021